Pengembangan Keberhasilan Usaha dengan Pendekatan Sociopreneur di Era Kenormalan Baru - Riskon Ginting; Yanita Ella Nilla Chandra; Yumna Nur Shabrina (JEMBATAN, 2021)
Social entrepreneurship, also known as sociopreneurship, is one approach to overcoming community entrepreneurship challenges such as financial constraints, managerial abilities, limited networks, and a lack of government attention. The purpose of this research is to increase the sociopreneur potential of the SME sector in Beji, Depok City in The New Normal Era. This study employs a quantitative approach with explanatory research methods based on inferential statistics. In this study, the population consisted of all communities in Beji District, Depok City. The study of multiple linear regression analysis included data analysis. The results of this study indicate that the variable that has a positive and significant influence on business success is socio-innovation.